Study of the interaction of Huperzia saururus Lycopodium alkaloids with the Acetylcholinesterase enzyme - Puiatti, Marcelo (2013)
In the present study, we describe and compare the binding modes of three Lycopodium alkaloids (sauroine, 6-hydroxylycopodine and sauroxine; isolated from Huperzia saururus) and huperzine A with the enzyme acetylcholinesterase. Refinement and rescoring of the docking poses (obtained with different programs) with an all atom force field helped to improve the quality of the protein?ligand complexes. Molecular dynamics simulations were performed to investigate the complexes and the alkaloid´s binding modes. The combination of the latter two methodologies indicated that binding in the active site is favored for the active compounds. On the other hand, similar binding energies in both the active and the peripheral sites were obtained for sauroine, thus explaining its experimentally determined lack of activity. MM-GBSA predicted the order of binding energies in agreement with the experimental IC50 values